Novel Microtubule targetting agents, pyrrolo-1,5,benzoxazepines induce apoptosis in multi-drug-resistant cancer cells - LLOYD, DAVID; ZISTERER, DANIELA; WILLIAMS, DAVID; FAYNE, DARREN (My University, 2010)
PURPOSE: The development of multi-drug resistance (MDR) due to the expression of members of the ATPase binding cassette (ABC) transporter family is a major obstacle in cancer treatment. The broad range of substrate specificities associated with these transporters leads to the efflux of many anti-cancer drugs from tumour cells. Therefore, the development of new chemotherapeutic agents that are not substrates of these transporters is important. We have recently demonstrated that some members of a novel series of pyrrolo-1,5-benzoxazepine (PBOX) compounds are microtubule-depolymerising agents that potently induce apoptosis in several cancer cell lines and impair growth of mouse breast tumours. The aim of this current study was to establish if PBOXs were capable of inducing apoptosis in cancer cells expressing either P-glycoprotein or breast cancer resistance protein (BCRP), two of the main ABC transporters associated with MDR. METHODS: We performed in vitro studies to assess the effects of PBOXs on cell proliferation, cell cycle and apoptosis in human cancer cell lines and their drug-resistant substrains expressing either P-glycoprotein or BCRP. In addition, we performed a preliminary molecular docking study to examine interactions between PBOXs and P-glycoprotein.
PUBLISHED
PMID 20020128
Keywords: Biochemistry; Oncology; microtubule-targeting agents; multi-drug resistance (MDR); P-glycoprotein; BCRP; Cancer